The North Atlantic in the greenhouse - overturning response and sensitivities - Schweckendiek, Ulf (2003)
The response of the thermohaline circulation (THC) in climate models on global warming scenarios differs fundamentally. To examine the role of the ocean component for this deviating behaviour,diagnosed fluxes from coupled greenhouse gas simulations are used to drive a regional model of the Atlantic Ocean. The results demonstrate, that the general response of the THC due to changes in atmospheric forcing is quite robust and insensitive to the improved representation of the ocean component. In order to test the crucial mechanisms for the evolution of the meridional overturning, sensitivity studies are by focussing on different combinations of surface fluxes are performed. The response indicates that the density in the Nordic Seas and subsequently the overflow waters determine trends and long-term variability of the overturning circulation, underlining the importance of that region for the THC. Deep water formation within the Labrador Sea, responsible for interannual to decadal variability is quite sensitive to anthropogenic changes in the surface fluxes, so that its convection eventually breaks down under surface warming and freshening.